2019
DOI: 10.4153/s0008414x19000075
|View full text |Cite
|
Sign up to set email alerts
|

On the Fourier Transformability of Strongly Almost Periodic Measures

Abstract: In this paper we characterize the Fourier transformability of strongly almost periodic measures in terms of an integrability condition for its Fourier Bohr series. We also provide a necessary and sufficient condition for a strongly almost periodic measure to be a Fourier transform of a measure. We discuss the Fourier transformability of a measure on R d in terms of its Fourier transform as a tempered distribution. We conclude by looking at a large class of such measures coming from the cut and project formalis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Finally, since S is weakly uniformly discrete, it follows that ν is translation bounded. Now, since the measure μ is tempered and its Fourier transform as a tempered distribution is a translation‐bounded measure, μ is Fourier transformable as a measure, by [44, Theorem 5.2]. The same statements hold for the measure ν, and we have μ̂=ν as claimed.…”
Section: Specific Results For G=double-struckrdmentioning
confidence: 59%
See 2 more Smart Citations
“…Finally, since S is weakly uniformly discrete, it follows that ν is translation bounded. Now, since the measure μ is tempered and its Fourier transform as a tempered distribution is a translation‐bounded measure, μ is Fourier transformable as a measure, by [44, Theorem 5.2]. The same statements hold for the measure ν, and we have μ̂=ν as claimed.…”
Section: Specific Results For G=double-struckrdmentioning
confidence: 59%
“…In previous sections, we have assumed our measures to be translation bounded and Fourier transformable. The connection between the distributional Fourier transform and Fourier transformability as an unbounded Radon measure, as we have considered, was clarified in [44], where it was shown that a measure μ on Rd is Fourier transformable as a measure if and only if it is tempered and its distributional Fourier transform is a translation‐bounded measure. Thus, in the Euclidean setting, a measure μ is translation bounded and Fourier transformable if and only if its distributional Fourier transform ν is a translation‐bounded and Fourier‐transformable measure.…”
Section: Specific Results For G=double-struckrdmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we consider the important special case of measures with uniformly discrete support, for which the three key notions turn out to be equivalent. This class is particularly relevant in the theory of aperiodic order, with several applications to mathematical quasicrystals and Meyer sets; see [4,8,11,12,14,17,18] and references therein.…”
Section: Proof Define the Non-negative Functionsmentioning
confidence: 99%